Impact of due process policy on construction projects delivery in Nigeria - Ameh, O.J.; Ogundare, O. (Penerbit UKM, 2013)
Public procurement system in Nigeria has over the years been grossly abused leading to cost inflation,delay in project delivery, poor quality of work, and project abandonment. The aim of this study is to examine the impact of the Due Process Policy on construction projects delivery in Nigeria. Data were collected using a structured questionnaire distributed to 52 random selections of contracting, consulting and public organisations operating in Lagos Nigeria. Data were analysed using descriptive statistics. The results show that due process policy has a very positive impact in Nigeria’s procurement terrain. Adherence to due process proceedings had highest impact on cost savings, prequalification of contractors and detailed project design, quality of project delivery, and project duration. The study serve as a feedback to the construction stakeholders in Nigeria and contains useable information for optimizing the existing due process mechanism to enhance not only probity, accountability, transparency and competition in public contract awards, but also the policy’s resultant effects on quality of executed projects, delivery-on-budget and time considerations.